Programmable spatial magnetization stereolithographic printing of biomimetic soft machines with thin-walled structures - Xianghe Meng; Shishi Li; Xingjian Shen; Chenyao Tian; Liyang Mao; Hui Xie (Nature Communications)
Abstract Soft machines respond to external magnetic stimuli with targeted shape changes and motions due to anisotropic magnetization, showing great potential in biomimetic applications. However, mimicking biological functionalities, particularly the complex hollow structures of organs and their dynamic behaviors, remains challenging. Here, we develop a printing method based on three-dimensional uniform magnetic field-assisted stereolithography to fabricate thin-walled soft machines with internal cavities and programmable magnetization. This printing technique employs Halbach arrays and an electromagnetic solenoid to generate an adjustable uniform magnetic field (up to 80 millitesla), efficiently orienting ferromagnetic particles, followed by solidification with patterned ultraviolet light. A support strategy and optimized material composition enhance printing stability and success rates. Our developed method enables fabrication of magnetic-driven soft machines capable of peristaltic propulsion, unidirectional fluid transport, periodic pumping action, and intake-expulsion deformation. These structures, achieving hollow ratios as high as 0.92 and enabling parallel manufacturing, highlight this technique’s considerable potential for biomedical applications by emulating complex biological behaviors and functions.